A randomized trial of rotavirus vaccine versus sucrose solution for vaccine injection pain. Issue 25 (9th June 2015) - Taddio, Anna; Flanders, Daniel; Weinberg, Eitan; Lamba, Supriya; Vyas, Charmy; Ilersich, Andrew F.; Ipp, Moshe; McNair, Carol
Abstract: Objective: Sucrose solutions are analgesic in infants. Oral rotavirus vaccine contains sucrose, however, it is not known if it possesses analgesic properties. The objective was to compare the analgesic effectiveness of rotavirus vaccine to sucrose solution when administered prior to injectable vaccines. Methods: Infants 2–4 months of age receiving oral rotavirus vaccine and two separate injectable vaccines on the same day were randomized to rotavirus vaccine (Rotarix™) first followed by the injectable vaccines and sucrose (Tootsweet™) afterwards, or vice versa. Pain was assessed by blinded raters using the Numerical Rating Scale (NRS, range 0–10) (parents, clinicians), or Modified Behavioural Pain Scale (MBPS, range 0–10) and cry duration (observers). Data were analyzed using t -tests or χ 2 -tests; Bonferroni correction was applied to correct for multiple comparisons, as appropriate. Results: Altogether, 120 infants participated: 60 were randomized to rotavirus vaccine first. Groups did not differ in demographics, including; age ( p  = 0.448) and sex ( p  = 0.464). The mean pain score (standard deviation) for both vaccine injections did not differ between infants given rotavirus vaccine first versus sucrose solution first: observer MBPS, parent NRS and clinician NRS scores were 7.4 (1.6) vs. 7.7 (1.6), 4.9 (2.1) vs. 5.8 (2.1), and 4.2 (2.1) vs. 4.6 (2.2), respectively. Similarly, there was no difference between groups in cry duration. Conclusion: Rotavirus vaccine did not differ from sucrose solution in reducing injection-induced pain. Based on the findings, it is recommended that rotavirus vaccine be administered prior to injectable vaccines in infants aged 2 and 4 months.